Monetization of ecosystem services for agrifood production systems - Joshi, Himanshu; Ansari, M. A.; Ravisankar, N.; Ansari, M. H.; Kumar, Sunil (Indian Farming, 2025)
Indian agrifood systems rely heavily on ecosystem services (ES) that underpin agricultural productivity and ecological sustainability. In India, monetizing ES, such as through payment for ecosystem services (PES), has emerged as a strategy to promote sustainable agricultural practices aligning with climate-smart goals, and support policy-making. Further, monetizing ES contributes to added capitalizable environmental benefits such as carbon sequestration, improved water & soil resource management, biodiversity conservation, coastal protection, etc. The presented work highlights the applicability of key approaches typically employed for the valuation of ES such as market-based valuation, cost-based approaches, and willingness-to-pay models. Further, it also underscores successful pilot PES implementations across the country. However, challenges persist, including data scarcity, lack of standardized methodologies, and risks of inequity, often marginalizing smallholder farmers. To scale PES programs, a unified National PES Policy coupled with technological interventions like GIS and blockchain, and public-private partnerships are critical. Further, community involvement, cultural alignment, and robust institutional frameworks are also requisite for ensuring equitable benefit-sharing and fostering widespread adoption of sustainable agri-practices.